Microbiological Water Safety of Community-Managed Drinking-Water Systems in Tirana - Spahiu, Erneleva (Richtmann Publishing, 2012)
Diseases related to contaminated drinking water have a greater impact on human health. The purpose of this study ismonitoring the microbiological characteristics of water dissolved in the water distribution system in Tirana. The method used formicrobiological analysis is: membrane filter. This method is based on filtering the water with a vacuum filter equipment using membranefilters with a diameter of 47 â€“ 50 mm, and 0.45 ô€ˆm pore size. As object of this study have been some areas of Tirana: Kinostudjo,Porcelan, Don Bosko, Kombinati, LaprakÃ«, 21 Dhjetori, Komuna e Parisit, Treni, Ali Demi, Yzberishti, Sharra, ect. The areas are codifyas : (A1, A2, A3, A4, A5,A6, A7, A8, A9, A10, A11, A12, A13, A14, A15, A16, A17, A18, A19, A20 ). Samples for analysis were takenfrom this areas in two stages with difference time a month of each other just to see the difference in microbial load depending ontemperature rise. Monitoring was conducted for indicator organisms (E. Coli, T. Count, Pseudomonas aeruginosa, Enterococcus fecalis).Mainly areas which result in a high contamination are codified as (A3, A4, A14, A17, A20). The reasons for these results are:amortization of distribution system, the lack of restoration of damaged items to the distribution system, illegal interference in thedistribution system, construction of wells in private homes, the use of storage systems and pumping systems for individual supply in anyresidential apartment.